2023
DOI: 10.1144/sp537-2022-205
|View full text |Cite
|
Sign up to set email alerts
|

Robust laser ablation Lu–Hf dating of apatite: an empirical evaluation

Abstract: Recent development in laser-ablation Lu-Hf dating has opened a new opportunity to rapidly obtain apatite ages that are potentially more robust to isotopic resetting compared to traditional U-Pb dating. However, the robustness of the apatite Lu-Hf system has not been systematically examined. To address this knowledge gap, we conducted four case studies to determine the resistivity of the apatite Lu-Hf system compared to the zircon and apatite U-Pb system. In all cases, the apatite U-Pb system records a secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
4
11
0
Order By: Relevance
“…A Rb–Sr down‐hole fractionation (DHF) correction was applied in LADR using the DHF behaviour of NIST‐610. Secondary reference materials Bund‐1b and Taratap were used for accuracy verification with reference ages of 286.2 ± 2.2 and 497.1 ± 0.6 Ma, respectively (Black, 2007; Glorie, Gilbert, et al., 2024; Glorie, Hand, et al., 2024). All Rb–Sr dates were calculated as inverse isochrons in IsoplotR (Vermeesch, 2018) using the Rb–Sr decay constant of 1.3972 ± 0.0045 × 10 −11 a −1 (Villa et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A Rb–Sr down‐hole fractionation (DHF) correction was applied in LADR using the DHF behaviour of NIST‐610. Secondary reference materials Bund‐1b and Taratap were used for accuracy verification with reference ages of 286.2 ± 2.2 and 497.1 ± 0.6 Ma, respectively (Black, 2007; Glorie, Gilbert, et al., 2024; Glorie, Hand, et al., 2024). All Rb–Sr dates were calculated as inverse isochrons in IsoplotR (Vermeesch, 2018) using the Rb–Sr decay constant of 1.3972 ± 0.0045 × 10 −11 a −1 (Villa et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The method involves the addition of NH 3 (supplied as a 1:9 NH 3 :He mix for safety reasons) into the reaction cell of the mass spectrometer (at a rate of 3 mL min −1 ) to promote efficient formation of the Hf((NH)(NH 2 )(NH 3 ) 3 ) + reaction product as a direct proxy for 176 Hf. Equivalent reaction products for isobars 176 Lu and 176 Yb are negligible, allowing 176 Hf and 176 Lu to be effectively separated and measured free from isobaric interferences (Glorie, Hand, et al., 2023; Simpson et al., 2021, 2022). Following Simpson et al.…”
Section: Methodsmentioning
confidence: 99%
“…Resulting Lu‐Hf dates were calculated as 2‐point (inverse) isochron ages in IsoplotR (Vermeesch, 2018), where the second point comprised an initial 177 Hf/ 176 Hf anchor of 3.55 ± 0.05, which spans the entire range of initial 177 Hf/ 176 Hf ratios of the terrestrial reservoir (e.g., Glorie, Hand, et al., 2023; Spencer et al., 2020). The obtained inverse isochron age for secondary reference material BP‐1 garnet was 1,752 ± 21 Ma (2σ uncertainty including propagated uncertainty from Hogsbo), which is in good agreement with previously published Lu‐Hf dates (1,745 ± 14 Ma and 1,744 ± 13 Ma; Glorie, Mulder, et al., 2023; Simpson et al., 2023, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…U-Pb system in apatite has been primarily used to constrain the timing of low-to moderate-temperature metamorphic and metasomatic processes (e.g., Kirkland et al 2017Kirkland et al , 2018Hall et al 2018;Henrichs et al 2018;Glorie et al 2019), with estimates for the U-Pb closure temperature from 375 to 550 °C (Schoene and Bowring 2007;Chew et al 2011;Cochrane et al 2014). However, recent advances utilising the Lu-Hf isotopic system have demonstrated the potential of apatite to date magmatic and higher temperature metamorphic processes (e.g., Barfod et al 2005;Simpson et al 2021;Gillespie et al 2022;Glorie et al 2022Glorie et al , 2023.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon for the Lu-Hf system in apatite to record older ages compared to the U-Pb system (e.g., Gillespie et al 2022;Glorie et al 2023;Kharkongor et al 2023), with estimates for the Lu-Hf closure temperature between 660 and 730 °C (Cherniak 2000;Barfod et al 2005;Chew and Spikings 2015;Glorie et al 2023). Lu-Hf dates recovered from predominantly undeformed granitoids are in general agreement with primary crystallisation ages obtained from magmatic and high-temperature metamorphic geochronometers such as zircon (e.g., Simpson et al 2021;Gillespie et al 2022;Glorie et al 2023). However, apatite is more susceptible to recrystallisation during deformation, and it has been shown that in-situ Lu-Hf dates from apatite in deformed rocks tend to reflect recrystallisation instead of primary magmatic crystallisation (Glorie et al 2023).…”
Section: Introductionmentioning
confidence: 99%